Schedule based material requirements planning: a case study of LCD TV manufacturer - Cheam, Kai Wen; Mohd Nor, Norasmiha; Shahkirin, Ahmad Haiqal; Jaafar, Muhamad Zamakhsyari; Mhd Zamaludin, Nabilah Afrina; Misnan, Nur Aini Nasihah (Penerbit UTHM, 2020)
The tools used by management to achieve its initial objectives is Production Planning and Control (PPC). PPC is used to propose the basic issues of utilization of its resources, inventory management and its low productivity. This is because the production system consists of four factors – quality, quantity, time and cost (Wikner J. O., 2000).